Development of Problem-Based Learning Devices for Training Science Process Skills (SPS) Junior High School Students - Ika Agrista; Endang Susantini; Widowati Budijastuti (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
One way to overcome undeveloped scientific process skills is by applying Problem Based Learning (PBL). PBL is a learning model that stimulates authentic problems for students to have Science Process Skills (SPS). This study aims to develop learning tools based on Problem Based Learning (PBL) on Environmental Pollution materials that are visible to be used to train students' Science Process Skills. The feasibility of learning is assessed based on validity, practicality and effectiveness. The type of research used is development by applying a 4-D model which includes the stages: Define, Design, Develop and Disseminate with extensive trials using the One group pretest-posttest design and tested on 15 students of class VII SMP Negeri 2 Gondang, Mojokerto Regency, for the 2020/2021 academic year. The data analysis technique used descriptive analysis or afferential statistic analysis. The results showed (1) the learning tools developed in the form of syllabus, lesson plans, worksheet, test about science process skills were included in the very valid category because have average≥ 3.60 . (2) The learning device shows practicality seen from the implementation of each activity which has a very good category and has a reliability coefficient > 75%, student activities also show a very valid category and statistical tests of the relationship and influence with the SPS value get sig < 0.05, the obstacles that accompanied by a solution. (3) Effective learning tools are assessed from the N-gain that reaches the medium and high categories with an average of > 0.80, the item sensitivity value is > 0.75, and the student's response shows an average of > 81% with a very good category. Based on the results of data analysis, it can be concluded that PBL-based learning tools on environmental pollution materials to train junior high school science process skills are valid, practical and effective to use learning activities in class.